Genetic Parameters and Diversity Studies Among Morphological Traits in Breeding Lines of Garlic (Allium Sativum L.) (Bangladesh Journal of Botany, 2023)
Thirty-four promising lines of garlic were grown in randomized block design with three replications under the latesown season in 2019-20 at Vegetable Research Farm of C. S. Azad University of Agriculture and Technology, Kalyanpur, Kanpur. The mean sum of squares showed highly significant differences among the lines for all the traits studied, indicating the presence of a sufficient amount of genetic variability. The moderate to higher magnitude of the coefficient of variation at genotypic as well as phenotypic levels was noticed for number of cloves per bulb, marketable bulb yield, average weight of bulb, average weight of cloves and plant height. High heritability coupled with high genetic advance as percent of mean was observed for plant height, leaf length, leaf width, polar diameter, number of cloves per bulb, average weight of bulb and average weight of cloves. Marketable bulb yield was positively and significantly correlated with the total bulb yield and dry matter content whereas, a significant negative correlation with leaf width. All the thirtyfour lines of garlic were grouped into five clusters based on Mahalanobis D2 statistics using Tocher’s method. The cluster II and V had among the moderate genetic distance having higher total bulb yield performance along with its contributing traits. The genotypes from cluster IV and V had the most divergent clusters and were suitable for high yielding garlic genotypes among the various advanced breeding lines under late sown conditions.Bangladesh J. Bot. 52(2): 225-233, 2023 (June)